Ichthyoplankton from the coasts of Jalisco and Colima, Mexico (December 1995 to December 1996) - C Franco-Gordo; R Flores-Vargas; C Navarro-Rodríguez; R Funes-Rodríguez; R Saldierna-Martínez (Ciencias Marinas, 1999)
The first check-list of marine fish larvae from the coasts of Jalisco and Colima (Mexico) is presented. The fish larvae were sorted from zooplankton samples collected with Bongo net during 11 oceanographic surveys between December 1995 and December 1996. A total of 102 taxa belonging to 50 families and 80 genera were identified. The families with the most number of species were Cynoglossidae, Carangidae and Paralichthydae. This collection represents the first step to future research on the biodiversity of fishes of this tropical region that has been little studied. The ichthyoplankton collection was catalogued and deposited in the Centro de Ecología Costera of the Universidad de Guadalajara, Mexico.